TECHNICAL ANALYSIS METHODS IN CRYPTOCURRENCY AND GOLD MARKETS: A COMPARATIVE PERSPECTIVE - Tukmirzaev Kamol Mumin ugli (Journals Park Publishing, 2025)
This study explores the application of technical analysis (TA) in two major asset classes: cryptocurrencies and gold. By analyzing key indicators, such as Fibonacci retracement levels, moving averages, and momentum oscillators, it evaluates their predictive power under different volatility and structure conditions. Empirical testing of experimental Fibonacci levels (e.g., 0.5993, 1.1987, -0.6993) shows improved accuracy in both markets, offering valuable insights for both institutional and retail traders.
Keywords: Cryptocurrency, gold market, technical analysis, fibonacci retracement, rsi divergence, adaptive indicators, market psychology, volatility.